Systematic Literature Review: EMR and Health Information Competence in Indonesia’s Digital Transformation - Bangkit Ary Pratama (Science Publication: Journal of Public Health and Nutrition, 2026)
ABSTRACT Digital transformation drives the use of health information systems to integrate clinical, administrative, and operational data. In Indonesia, diverse infrastructure, administrative models, and workforce competencies pose challenges to electronic medical records (EMR) implementation. This study aims to analyze EMR adoption and its implications for strengthening the competence of Health Information and Medical Record (HIMR) professionals in Indonesia’s digital transformation era. A systematic literature review was conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) protocol. The review followed four stages: identification, screening, eligibility, and inclusion. A total of 180 articles were initially retrieved from electronic databases, including Google Scholar, ResearchGate, and Garuda Kemdikbud. After applying inclusion and exclusion criteria, 21 studies were selected for the final analysis. Findings highlight variations in EMR effectiveness, HIMR competence, data ethics and security, and technical and organizational barriers. EMR improves efficiency and accuracy of clinical documentation, yet competence development is limited by disparities in digital literacy and regulatory understanding. Strengthening advanced authentication, infrastructure standardization, and standard operating procedure is essential to enhance HIMR technical and managerial capacity for sustainable system integration. Keywords: competence; digital transformation; electronic medical records; health information management; Indonesia